1990
DOI: 10.1080/00224545.1990.9924569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Deprivation on Learned Helplessness

Abstract: The influence of prolonged deprivation on response to uncontrollable outcome was investigated among 104 young Indian students. They received an unsolvable block design task followed by an anagram solution test and an attribution questionnaire. As predicted, the high-deprived and the female students displayed greater helplessness than their low-deprived and male counterparts, and they attributed uncontrollable outcome more to internal, stable, and global causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The employment domain was the second most salient in the ‘effect’ it exerted on depression symptoms. Experiments in social psychology have shown that prolonged deprivation along with basic needs not being satisfied can lead to feelings of incompetence and inefficiency as well as powerlessness and helplessness [ 39 ]. This in turn creates a perception of loss of control over one’s circumstances and often a sense of hopelessness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The employment domain was the second most salient in the ‘effect’ it exerted on depression symptoms. Experiments in social psychology have shown that prolonged deprivation along with basic needs not being satisfied can lead to feelings of incompetence and inefficiency as well as powerlessness and helplessness [ 39 ]. This in turn creates a perception of loss of control over one’s circumstances and often a sense of hopelessness [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, control deprivation has been hypothesized as playing an important role in a wide range of phenomena (Peterson, Maier, & Seligman, 1993), such as depression (Miller & Seligman, 1975;Seligman, 1975), aging (Baltes & Baltes, 1986;Fry, 1989;Langer & Rodin, 1976;Schulz, 1976), achievement problems in school (Diener & Dweck, 1978;Kofta, 1993), prolonged deprivation effects (Mal, Jain, & Yadav, 1990), and social class experience (Adler et al, 1994). This research implies that control deprivation could be a critical but underestimated factor in understanding social behavior.…”
Section: Effects Of Control Deprivation On Subsequent Use Of Stereotypesmentioning
confidence: 98%
“…If, for instance, a person were to identify depressed mood in their problem list, a formulating clinician should investigate processes of self-esteem maintenance (Brown, Bifulco and Andrews, 1990), learned helplessness and self-efficacy (Mal et al, 1990;Evans, Saltzman and Cooperman, 2001;Seligman, 1989) and the extensive literature on negative cognitive schemas (Beck et al, 1979;Kumari and Blackburn, 1992). These latter considerations should extend to interpersonal schemas (Young, 1999).…”
Section: Diagnosis and Formulationmentioning
confidence: 99%
“…The mediating psychological processes approach (Kinderman, 2005), of course, is not limited to cognitive processes. Behavioural mechanisms such as learned helplessness (Mal et al, 1990;Evans et al, 2001;Seligman, 1989) and classical conditioning (Dadds, Davey and Field, 2001), and interventions such as systematic desensitization (King, Muris and Ollendick, 2005), activity scheduling (Beck et al, 1979) and behavioural experiments (Bennett-Levy et al, 2004), and psychodynamic factors such as the role of family processes (Lopez et al, 2004) and relationships with formal and informal carers (Ryan, 2002) can be integrated into the formulation.…”
Section: Disruption To Psychological Processes or Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation